2021
DOI: 10.1080/21655979.2021.2001184
|View full text |Cite
|
Sign up to set email alerts
|

Polygonatum sibiricum polysaccharides (PSP) improve the palmitic acid (PA)-induced inhibition of survival, inflammation, and glucose uptake in skeletal muscle cells

Abstract: Polygonatum sibiricum polysaccharides (PSP) can decrease the levels of fasting blood glucose, total cholesterol, and triglyceride (TG) in hyperlipidemic and diabetic animals. It can also reduce inflammatory cytokines and promote glucose uptake in adipocytes. However, the underlying molecular mechanisms of PSP in improving insulin resistance (IR) in skeletal muscle remain unclear. In this study, palmitic acid (PA) induced an IR model in L6 myotubes. After treatment, cell proliferation was measured us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…To develop a PA-IR model, C2C12 myotubes were treated with 250 µM PA (Sigma-Aldrich, St. Louis, MO, USA) for 24 h, as described by Cai et al [ 26 ]. Briefly, PA was dissolved in ethanol and diluted to 1:10 in fatty acid-free (>98%) bovine serum albumin (BSA; Sigma; final concentration = 2% w / v ).…”
Section: Methodsmentioning
confidence: 99%
“…To develop a PA-IR model, C2C12 myotubes were treated with 250 µM PA (Sigma-Aldrich, St. Louis, MO, USA) for 24 h, as described by Cai et al [ 26 ]. Briefly, PA was dissolved in ethanol and diluted to 1:10 in fatty acid-free (>98%) bovine serum albumin (BSA; Sigma; final concentration = 2% w / v ).…”
Section: Methodsmentioning
confidence: 99%
“…Polygonatum has also been shown to attenuate myocardial fibrosis and inflammation and restore the morphology and function of myocardial tissue by regulating AMPK-Nrf2, NF-κB, TGF-β1/Smads, and NLRP3 inflammasome signaling pathway [ 152 – 157 ]. In addition, Polygonatum also has significant efficacy in lipid regulation and anti-atherosclerosis, which can prevent and control the occurrence of atherosclerosis by regulating metabolic abnormality, reducing lipid accumulation, inhibiting hyperglycemia, and reducing vascular damage, so as to intervene in the risk factors of CVDs [ 129 139 ]. Atherosclerosis is closely related to hyperlipidemia, inflammation, and oxidative stress, so it is clear that the pharmacological effects exerted by Polygonatum are intertwined.…”
Section: Discussionmentioning
confidence: 99%
“…PSPs was reported to reduce lipid accumulation and diminish the expression level of inflammatory factors in insulin-resistant cell models by regulating microRNA-140-5p/interleukin-1 receptor-associated kinase 3 (miR-340-3p/IRAK3), which plays a crucial role in inhibiting atherogenesis [ 129 ]. Different from the lipid-lowering effect of PSPs, other studies have revealed that steroid saponins and homoisoflavones extracted from Polygonatum have potential hypoglycemic effects [ 130 132 ], and the latter has been found to be able to inhibit the formation of advanced glycosylation end products [ 131 ].…”
Section: Introductionmentioning
confidence: 99%
“…M2-polarized macrophages are anti-inflammatory and protective, while M1-polarized macrophages are believed to have adverse effects on cells [ 21 ]. Previous research identified that compounds isolated from polygonatum had anti-inflammatory effects [ 22 , 23 ]. In the past, Liu et al found that PSPs could downregulate the LPS-mediated increase in neutrophil ratio and reduce the level of LPS-induced inflammatory factors in BALF of the rat ALI model [ 22 ].…”
Section: Discussionmentioning
confidence: 99%